Religious Education in the Mitigation Space: The Significance of the Muhammadiyah Enlightenment Movement for West Sulawesi Earthquake Survivors - Muhammad Alifuddin; Suarni; Alhamuddin, Alhamuddin; Ahmad Fanani (Jurnal Pendidikan Islam, 2022)
Purpose – This study aims to describe analytically the active religious education carried out by Muhammadiyah elements for earthquake survivors in Ahu, West Sulawesi. The research data were obtained through participatory observation, in-depth interviews, and document review. Design/methods/approach – All data obtained were analyzed using Miles and Huberman’s paradigm combined with Von Eckarberg’s hermeneutic phenomenological analysis model. Findings – The findings and discussion of this research conclude as follows; (1)The enlightenment movement in the field of religious education for survivors in Ahu Village is an integral part of the disaster mitigation program by Muhammadiyah. MDMC volunteers implemented the program for early childhood, kindergarten, and primary education, as well as for groups of survivors from among adults. The religious education program is non-formal, and its implementation uses a contextual learning approach. (2) The religious education program for the survivors is significant, not only because of the process of transferring knowledge but also the process of mental and spiritual enlightenment for the survivors. This process enables the survivors to be more assertive and patient and can respond positively to the reality of the disaster that befell them. (3) Conceptually, the enlightenment movement through active religious education carried out by MDMC can be categorized as a disaster risk reduction effort that is non-physical and is part of the concept of disaster mitigation. Research implications/limitations – Thus, this research is expected to have implications for efforts to develop a mitigation model based on religious education for survivors. Practical implications – The entire series of religious education processes carried out by MDMC for survivors, conceptually or in scientific theory, has meaning or is very significant in shaping survivors’ mental attitudes and religiosity.